The City's Image in Muourid Al-Barghouti's Fictional Biography "I Saw Ramallah" - Abu Own, Amal Mahmoud (Journal of Arabic Language Sciences and Literature, 2022)
This research discusses the image of "Ramallah" in Mourid Al-Barghouti's fictional biography "I Saw Ramallah " to spot light on the city's transformations in the Palestinian novel. He described Ramallah at a pivotal moment in the history of the Palestinian cause, which impacted the writers' attitude towards the occupied city of Ramallah, as it became the center of the new Palestinian National Authority. Al-Barghouti resorted to make a comparison between the city's image in his mind by recalling his memories and its current image. He, thus, painted an image of the city in two different phases: the first before (the Naksa) in 1967, and the second after (Oslo) in 1993. The researcher used the descriptive analytical method. Because its convenient for comparison, and helps to reach conclusions from the available data.The research reviewed the image of Ramallah as it appeared in the biography between these two phases (before the Naksa and after Oslo) with its different temporal, spatial, social, and political dimensions and the city's relationship with the countryside. And it presented the most important transformations that occurred in the city after Oslo; the most prominent of which was the political aspect, in addition to presenting Al-Barghouti's position from the city in the two phases.
Keywords: Ramallah; City Transformations; Palestinian Novel; Fictional Biography